A multi-satellite study of magnetic pulsations associated with a storm sudden commencement (SSC) as observed at syochronous orbit - Sakurai, Tohru; Tonegawa, Yutaka; Tomomura, Kiyoshi; Kato, Yoshio (1984)
P(論文) Oscillation characteristics of ultra-low frequency (ULF) hydromagnetic waves at synchronous orbit in response to a storm sudden commencement (SSC) are studied on the basis of the magnetic field observed on March 23,1975,simultaneously by the three synchronous satellites, SMS-1,SMS-2 and ATS-6,20 degrees apart from one another in longitude. The oscillations exhibited dampedtype, quasi-sinusoidal oscillations. They were purely transverse and azimuthally polarized, indicating a toroidal mode oscillation. The characteristics of the pure toroidal mode oscillation were emphasized with a drastic change of the oscillation component of the magnetic field perturbation from the radial (V) to the azimuthal (D) direction in association with the SSC. The oscillations appeared as a harmonic structure in the frequency. The dominant harmonics were odd ones, i. e. 1st, 3rd, etc. Furthermore, the frequencies of the harmonics observed at each satellite showed a clear local time dependence. In conclusion, the present study verifies that the ULF waves in association with the SSC on March 23,1975 in the afternoonside of the magnetosphere behaved as a clear standing oscillation of toroidal mode of the field line resonance excited by the SSC. departmental bulletin paper